Intracranial Arterial Dolichoectasia and Stenosis: Risk Factors and Relation to Cerebral Small Vessel Disease. Issue 5 (May 2018) - Zhai, Fei-Fei; Yan, Shuang; Li, Ming-Li; Han, Fei; Wang, Quan; Zhou, Li-Xin; Ni, Jun; Yao, Ming; Zhang, Shu-Yang; Cui, Li-Ying; Jin, Zheng-Yu; Zhu, Yi-Cheng
Abstract : Background and Purpose—: Intracranial arterial dolichoectasia (IADE) is a poorly understood arteriopathy compared with intracranial atherosclerotic stenosis (ICAS). We aimed to investigate the risk factors of IADE and ICAS and their relationship with neuroimaging markers of cerebral small vessel disease in a population-based study. Methods—: This study comprised 1237 participants (aged 57.2±9.4 years, 37.6% men) who underwent brain magnetic resonance imaging and magnetic resonance angiography. IADE was assessed based on basilar artery dolichoectasia (diameter, height of bifurcation, and laterality of basilar artery) and dilation of basilar artery and internal carotid artery (intracranial volume-adjusted diameter ≥2 SD). ICAS was defined as any degree of stenosis in at least 1 intracranial artery. The neuroimaging markers of cerebral small vessel disease, including lacunes, white matter hyperintensities, microbleeds, dilated perivascular spaces, and brain atrophy, were evaluated. Results—: Basilar arterial dolichoectasia was observed in 3.6% (45/1237); intracranial arterial dilation in 5.9% (67/1142); and ICAS in 15.7% (194/1237). Older age, higher systolic blood pressure, diabetes mellitus, higher LDL-C (low-density lipoprotein cholesterol) and lower HDL-C (high-density lipoprotein cholesterol) were associated with the presence of ICAS (all P <0.001), whereas only older age was associated with IADE. ICAS was associated with lacunes (odds ratio, 2.91; 95% confidence interval, 1.96–4.34; P <0.001), increased white matter hyperintensities volume (β±SE, 0.54±0.13; P <0.001), and brain atrophy (β±SE, −1.16±0.21; P <0.001), whereas basilar arterial dolichoectasia was mainly associated with dilated perivascular spaces in basal ganglia (odds ratio, 2.20; 95% confidence interval, 1.20–4.02; P =0.01) and, to a lesser extent, associated with lacunes and microbleeds. Conclusions—: IADE and ICAS had different risk factor profiles and associated with different imaging phenotypes of cerebral small vessel disease, suggesting different underlying mechanisms. Abstract : Supplemental Digital Content is available in the text.